2020
DOI: 10.1177/0020764020944200
|View full text |Cite
|
Sign up to set email alerts
|

Mental health in biological disasters: From SARS to COVID-19

Abstract: Background: The outbreak of coronavirus disease 2019 (COVID-19), like severe acute respiratory syndrome (SARS), provokes fear, anxiety and depression in the public, which further affects mental health issues. Taiwan has used their experience of the SARS epidemic for the management of foreseeable problems in COVID-19 endemic. Aim/Objective: This review summarizes issues concerning mental health problems related to infectious diseases from current literatures. Results: In suspected cases under quarantine, confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 63 publications
1
38
1
3
Order By: Relevance
“…Keywords: adolescent, COVID-19, mask, psychological problems, SARS-CoV-2, school BACKGROUND Several studies have shown that severe infectious disease outbreaks affecting multiple countries and communities can impact not only physical but also psychological health (1)(2)(3). Although positive changes and cognitive restructuring were described in some cases, generally, a series of negative consequences was evidenced.…”
mentioning
confidence: 99%
“…Keywords: adolescent, COVID-19, mask, psychological problems, SARS-CoV-2, school BACKGROUND Several studies have shown that severe infectious disease outbreaks affecting multiple countries and communities can impact not only physical but also psychological health (1)(2)(3). Although positive changes and cognitive restructuring were described in some cases, generally, a series of negative consequences was evidenced.…”
mentioning
confidence: 99%
“…La alteración de la rutina puede llegar a provocar problemas de salud mental como frustración por la sensación de dejar de hacer algo, ansiedad y temores (Hsieh et al 2020;Koushik, 2020;Pastor, 2020;Serafini et al 2020), así como otros factores psicosociales relacionados con el estrés y depresión (Apaza et al 2020) además, la pérdida del contacto diario con los colegas y amigos causa frustración y apatía (Brooks et al 2020). El confinamiento genera la aparición de diversas manifestaciones (Dorrance et al 2020), como la frustración por actividades negadas, una sensación de falta de libertad, la ausencia física de los amigos, entre otros; además de otros efectos sociales y económicos, como pueden ser la pérdida de trabajos, de emprendimientos, etc.…”
Section: Dinámica Familiar En Tiempos De Pandemiaunclassified
“…According to Hsieh et al (2020), SARS affected healthcare professionals more than the general populace. This was attributed to SARS's unique trail of transmission and considering that the virus was mostly concentrated in healthcare settings (Hsieh et al, 2020;Stuijfzand et al, 2020;Centers for Disease Control and Prevention [CDC], 2003;Lee et al, 2003).…”
Section: Mental Health Services During Pandemics: Challenges and Interventionsmentioning
confidence: 99%
“…Other issues that affect healthcare workers during pandemics were highlighted by Hsieh et al (2020), Thobaity and Alshammari (2020) and Stuijfzand et al (2020) and they include changes in everyday tasks which can lead to stress, fear of infection, economic loss, lifestyle changes, changes in work schedules and undesirable mental health outcomes (sleep problems, anxiety and suicide). As the pandemic progresses, psychiatric healthcare professionals will have more worries in line with the care of patients in the wake of limited resources and the sufficiency of their own protection from COVID-19.…”
Section: Mental Health Services During Pandemics: Challenges and Interventionsmentioning
confidence: 99%